Training of teachers in the context of the first Republic in Portugal: guidelines for understanding of a policy - António Gomes Ferreira; Luís Mota (FahrenHouse, 2014)
In this paper we set out to study teacher training in the framework of the First Republic of Portugal (1910-1926). Republicanism embodied a project of the refounding of the nation, which found in education the means of achieving such aspiration. Believing in human plasticity, it elected education, aligned with scientific development, through the path of schooling, as the tool for shaping the new Republican citizen. Teachers had a crucial part to play in this project. Addressing legislation, file sources (exercises, summary books, assignments, inter allia), printed sources (books, workbooks, etc.) and specialised media on education and teaching, we discuss training programmes for primary and secondary education teachers. We look into the virtues of its implementation and submit our reading thereof, comparing regular primary education to regular teacher training. We conduct an in depth analysis of the curricula and the training guidelines, focusing in particular on the study plans and their components, from scientific education, the specialisation in the area of expertise and psycho-pedagogy, to teaching practice. Received:  26/10/2013 / Accepted: 17/11/2013 How to reference this article Gomes Ferreira, A., Mota, L. (2014). Formación de profesorado en el contexto de la Primera República en Portugal: pautas para la comprensión de una política. Foro de Educación, 12(17), pp. 45-68. doi: http://dx.doi.org/10.14516/fde.2014.012.017.003